The Prevalence of Aortic Arch Anomalies in Children Who Underwent Cardiac Catheterization: A Single-center Experience - Ferit Kulalı; Utku Örün; Tamer Yoldaş; Selmin Karademir; Vehbi Doğan; Senem Özgür (Galenos Publishing House, 2019)
INTRODUCTION: We aimed to determine the prevalence of aortic arch anomalies in children who underwent cardiac catheterization and angiography for various reasons. METHODS: 1928 patients who underwent diagnostic or interventional cardiac catheterization and angiocardiography were retrospectively evaluated and 198 patients who had aortic arch anomalies were included in our study. Diagnosis was established by transthoracic echocardiography and angiography. RESULTS: Of 1928 patients who underwent diagnostic or interventional cardiac catheterization, 198 (10.3%) had aortic arch anomalies. Ages of 198 patients (10.3%) with aortic arch anomalies ranged from one day to 192 months (mean 37.7 +- 42.8 months). Of these patients, 36,9% had tetralogy of Fallot, 23.8% had ventricular septal defect, 12.2% had double outlet right ventricle, 6.6% had transposition of the great arteries, and 20.5% had other anomalies. The commonest symptoms were cyanosis, murmur, wheezing, and recurrent lung infections. On physical examination, the most common sign was a murmur (95.5%). The commonest aortic arch anomaly was the right aortic arch (61.1%) followed by the normal left aortic arch and its variations (23.2%). DISCUSSION AND CONCLUSION: The prevalence of aortic arch anomalies varies depending on gender and accompanying congenital heart disorders.